2005
DOI: 10.1295/polymj.37.767
|View full text |Cite
|
Sign up to set email alerts
|

Tribological Properties of Poly(methyl methacrylate) Brushes Prepared by Surface-Initiated Atom Transfer Radical Polymerization

Abstract: ABSTRACT:Surface-initiated living radical polymerization of methyl methacrylate (MMA) using copper/bipyridyl complex was carried out from silicon wafer immobilized with a 2-bromoisobutylate moiety, resulting in the assembly of polymer chains tethered by one end to a surface, a so-called ''polymer brush''. The thickness of the PMMA brush, which was estimated by ellipsometry and atomic force microscopy, increased linearly with the molecular weight of the chains, and was controlled by the free initiator concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
103
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 100 publications
(105 citation statements)
references
References 38 publications
2
103
0
Order By: Relevance
“…Furthermore, most previous research on the friction of grafted polymers has been carried out at very low normal force conditions, which are quite different from practical conditions. The authors have previously synthesized high-density PMMA brush on a flat silicon substrate [38] and have found that polymer brush affords a lowfriction and wear-resistant surface under a high normal load [39]. Therefore, hydrophilic polymer brush can be expected to give a low friction surface under wet conditions.…”
Section: Preparation and Physicochemical Properties Of Highdensity Pomentioning
confidence: 99%
“…Furthermore, most previous research on the friction of grafted polymers has been carried out at very low normal force conditions, which are quite different from practical conditions. The authors have previously synthesized high-density PMMA brush on a flat silicon substrate [38] and have found that polymer brush affords a lowfriction and wear-resistant surface under a high normal load [39]. Therefore, hydrophilic polymer brush can be expected to give a low friction surface under wet conditions.…”
Section: Preparation and Physicochemical Properties Of Highdensity Pomentioning
confidence: 99%
“…One possible method to overcome this weak adhesion is the immobilization of fluorinated polymer onto the substrate. Actually, spin-cast films are easily scratched out by friction or rubbing, though the tethered polymer surface shows good wear resistance 12 because the polymer chain ends are covalently bound with substrate. Polymer chains tethered to a surface or interface with a sufficiently high grafting density are referred to as ''polymer brush.''…”
mentioning
confidence: 99%
“…Generally speaking, the immobilization of initiators is achieved by forming initiator-containing SAMs on the substrate. For instance, Takahara et al has prepared covalently tethered poly(methyl methacrylate) (PMMA) brushes on the Si wafer immobilized with an initiator SAMs of 2-bromoisobutylate moiety, abridged as DMSB (Fig. www.intechopen.com 19a) (Sakata et al, 2005). Compared with the spin-coated PMMA film, the self-assembled PMMA brush is found possessing much better wear resistance (Fig.…”
Section: Polymer Samfsmentioning
confidence: 99%